Analisis ANALISIS PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MENGGUNAKAN MODEL INKUIRI TERBIMBING BERDASARKAN N-GAIN - Tania Oktatinari; An Nuril Maulida Fauziah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the improvement of students’ critical thinking skills through the implementation of the guided inquiry learning model. This research used a quantitative approach with a pre-experimental design in the form of one group pretest-posttest. The subjects were 30 students of class VIII-B at SMP Negeri 5 Surabaya in the 2025/2026 academic year. The instruments used included critical thinking tests, observation sheets of learning implementation, and student response questionnaires. Data were analyzed using N-Gain, normality test, paired sample t-test, and Wilcoxon test. The results showed that the average N-Gain score was 0.82 (high category). A total of 77% of students were in the high category and 23% in the medium category. Learning implementation reached 100% (very good), and student responses were in the very good category. Thus, the guided inquiry learning model is effective in improving students' critical thinking skills.